Positive computing : technology for wellbeing and human potential - Calvo, Raefael A., ....-; Peters, Dorian, ....- (Cambridge : MIT Press, 2014)
On the eve of Google's IPO in 2004, Larry Page and Sergey Brin vowed not to be evil. Today, a growing number of technologists would go further, trying to ensure that their work actively improves people's lives. Technology, so pervasive and ubiquitous, has the capacity to increase stress and suffering; but it also has the less-heralded potential to improve the well-being of individuals, society, and the planet. In this book, Rafael Calvo and Dorian Peters investigate what they term "positive computing" -- the design and development of technology to support psychological well-being and human potential. Calvo and Peters explain that technologists' growing interest in social good is part of a larger public concern about how our digital experience affects our emotions and our quality of life -- which itself reflects an emerging focus on humanistic values in many different disciplines. Synthesizing theory, knowledge, and empirical methodologies from a variety of fields, they offer a rigorous and coherent foundational framework for positive computing. Sidebars by experts from psychology, neuroscience, human--computer interaction, and other disciplines supply essential context. Calvo and Peters examine specific well-being factors, including positive emotions, self-awareness, mindfulness, empathy, and compassion, and explore how technology can support these factors. Finally, they offer suggestions for future research and funding.
Keywords: Technologie